PENGARUH RETURN ON ASSETS,RETURN ON EQUITY DAN CURRENT RATIO TERHADAP HARGA SAHAM PAFA PERUSAHAAN PERTAMBANGAN SEKTOR BATUBARAYANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - machmudah, Naili; sudarsono, Bambang (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
The purpose of this study was to determine the influence Return on Assets, Return On Equity, and Current Ratio in coal sector mining companies on the Indonesia Stock Exchange (IDX), both partially and simultaneously on stock prices. This research uses quantitative methods. Using multiple linear regression analysis. The data in this research uses secondary data obtained from the Indonesia Stock Exchange (IDX). The sample was taken using a purposive sampling method, and a sample size of 12 companies from 19 companies was obtained. Hypothesis testing was carried out using multiple linear analysis. The results of the F test show that Return On Assets, Return On Equity, and Current Ratio have a positive and significant influence on stock prices and the results of the T test show that partially Return On Assets have a positive and significant influence on stock prices, Return On Equity has a positive and significant influence on stock prices, and the Current Ratio have a positive and significant influence on stock prices, the coefficient of determination (R^2) is 0.527, which means the independent variable is able to explain the dependent variable by 52.7% while the rest is explained by other variables not included in this research.Keywords: Return On Assets (ROA), Return On Equity (ROE), Current Ratio (CR, and Stock Price